Effect of Incudostapedial Reconstruction Using Conchal Cartilage Interposition Graft on Hearing Outcome - Hameed,Nazrin (2019)
Abstract Introduction Chronic otitis media is a widely prevalent condition in developing countries and is a cause of correctable hearing loss. The most frequent ossicular chain defect found during surgery for chronic otitis media has been a discontinuity of the incudostapedial joint. This study observes the effect of incudostapedial reconstruction using conchal cartilage on the hearing of the patient. Objectives To evaluate improvement in hearing by incudostapedial reconstruction using conchal cartilage interposition graft in tympanoplasty and to identify the independent factors associated with erosion of the long process of incus among patients with chronic suppurative otitis media tubotympanic type. Methods This study was conducted in the department of ear, nose and throat (ENT) amongst 22 patients with tubotympanic-type chronic suppurative otitis media who were found to have erosion of the long process during tympanoplasty. These patients underwent incudostapedial reconstruction using conchal cartilage. Their hearing was again reassessed at 12 weeks postsurgery, and the changes were observed. Results A statistically significant improvement in air conduction by 15.14 dB was found after undergoing incudostapedial reconstruction using conchal cartilage (p < 0.001). There was no statistically significant change in bone conduction (p value > 0.05). A total of 59.1% of patients in the study had an improvement in hearing ranging from11 to 20 dB. It was also found that 50% of the patients had a postoperative hearing of 10 to 20 dB. Conclusion Conchal cartilage interposition graft effectively improved hearing when used for the reconstruction of the incudostapedial joint during tympanoplasty in patients of chronic suppurative otitis media.